METHODOLOGY FOR THE FORMATION OF SPEECH COMPETENCE IN PRIMARY SCHOOL STUDENTS BASED ON AN INTEGRATIVE APPROACH (World Bulletin of Education and Learning, 2025)
This article describes in detail the general features of an integrative approach to the development of speech competence in primary school students.
Keywords: Competence, integration, integrative approach, logical games.